A Study on the Prevalence of Klebsiella pneumoniae and its Antibiotic Resistance Patterns from Urine of Students in a Tertiary Institution - Ugwu, Celestina Chibuzo (Microbiology and Biotechnology Research: An Overview Vol. 3, 2025)
Background/Introduction: Antimicrobial resistance (AMR) among microorganisms is a public health problem, especially in underdeveloped countries. Antibiotic-resistant bacterial infections, particularly those caused by multidrug-resistant (MDR) strains, can result in major health issues such as extended hospital stays, unsuccessful treatments, and even death. Klebsiella pneumoniae is a common bacterium responsible for many cases of urinary tract infections (UTIs). The growing resistance of this organism to various antibiotics is reducing the number of effective treatment choices. Aims and Objectives: The aim of this study is to ascertain the occurrence and antibiotic resistance patterns of Klebsiella pneumoniae isolated from the urine of students in a tertiary institution. Materials and Methods: The Experimental non-randomised trial research design was used in this research work. The study was conducted at the Department of Applied Microbiology of Enugu State University of Science and Technology, Enugu State, Nigeria. A total of 67 urine samples were collected aseptically from apparently healthy students. A loopful of each urine sample was inoculated on MacConkey agar for significant bacterial growth. The isolates were identified using standard microbiological procedures. Results: Results showed a mean bacterial load of 1.7×104 cfu/ml from males and 2.1×104 cfu/ml from females. Out of 67 urine samples collected, 17 (25.37%) yielded positive growth of Klebsiella pneumoniae. The male students had 6 (18.75%) from 32 urine samples, while female students had 11 (31.43%) from 35 urine samples. There was no significant difference (p>0.05) in the prevalence rates among the male and female students. Isolated organisms had varying degrees of resistance to the antibiotics used. Klebsiella pneumoniae from males had resistance to the following antibiotics: amoxicillin at 83.3%; streptomycin and ofloxacin at 50% respectively; cotrimoxazole, amoxicillin/clavulanic acid and pefloxacin at 66.67% respectively; gentamycin at 83.3% while Klebsiella pneumoniae from females had resistance on amoxicillin at 81.82%; streptomycin at 54.53%; sparfloxacin at 72.73%; ciprofloxacin at 63.64%. Generally, the isolates from females had more resistance to the antibiotics than the males. It was also observed that Klebsiella pneumoniae was resistant to more than two classes of antibiotics used in the study: \(β\)-lactam, quinolones and aminoglycosides. Multidrug resistance (MDR) index ranged from 0.1 to 0.5 for males and 0.2 to 0.9 for females. Conclusion: The high prevalence of Klebsiella pneumoniae and MDR index among the students in the study was a threat to their health and indicative of poor personal hygiene. To prevent antibiotic resistance, it is essential to carefully choose the right antibiotic and use it responsibly, following proper dosage and administration guidelines. Therefore, public enlightenment programmes should be carried out to educate them on the prevention of urinary tract infections.